Enrichment of functional microorganisms in AAO segmental influent-biofilm filler coupling process to improve the pollutants removal efficiency at low temperature. (October 2022) - Wang, Fan; Bian, Wei; Liu, Wenai; Liu, Songlin; Cui, Qin; Ai, Shengshu; Bian, Dejun
Abstract: In this study, a coupling anaerobic anoxic oxic (AAO) activated sludge-biofilm process with segmental influent was constructed to increase the concentration of functional microorganisms in the reactor and improve the efficiency of municipal wastewater treatment at low temperature, and investigated the pollutant removal pattern and microbial characteristics at low temperature. Conventional pollutants and sludge characteristics indicator were tested at the segmental influent flow distribution ratio of A1:O1 = 2:1. The study showed that the removal rates of chemical oxygen demand (COD), ammonia nitrogen (NH4 + -N), total nitrogen (TN), and total phosphorus (TP) were 89 %, 90.74 %, 76.60 %, and 96.60 %, in contrast to the conventional AAO process, at low temperature, COD degradation was concentrated in A1 and O1, simultaneous nitrification and denitrification (SND) occurred in O1 to achieve effective N removal, the phosphorus (P) significant removal in O1. The extracellular polymeric substances (EPS) content of activated sludge in the compartment was negatively correlated with the incoming COD content. And the distribution of carbon and nitrogen sources in the segmental influent contributed to the higher active activity of microorganisms and higher removal efficiency. The analysis of microbial communities in activated sludge and filler samples by Illumina high-throughput sequencing showed that the abundance and diversity of microbial communities in the biofilm were more significant than the activated sludge, and Proteobacteria were the most abundant phylum in the community. The presence of many denitrifying phylum such as Firmicutes and Nitrospira ensured the stability of the modified AAO system at low temperature. Dokdonella, Denitratisoma, Rhodoferax, and other genera ensured efficient phosphorus removal. Graphical abstract: Unlabelled Image Highlights: EPS content of the activated sludge in each reaction tank is inversely proportional to the COD concentration of the influent. Segmental water is beneficial for stimulating the microbial activity of the O1 compartment in AAO to improve pollutant removal efficiency. Dominant phosphorus removal bacteria, higher abundance genus of Tetrasphaera in activated sludge, high abundance genus of Candidatus_Accumulibacter in biofilms.